REPRESENTASI NILAI BUDAYA MINANGKABAU DALAM SERIAL SAIYO SAKATO: ANALISIS SEMIOTIKA ROLAND BARTHES - Handayani, Rika; Prathisara, Gibbran (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2026)
Abstract This study aims to analyze the representation of Minangkabau cultural values in the Saiyo Sakato series. The focus of this research includes the representation of deliberation and consensus, the matrilineal kinship system, the tradition of migration, the symbolism of traditional foods, and the use of the Minangkabau language in the context of modern life, particularly in relation to family economic issues. This study applies Roland Barthes’ semiotic approach through the analysis of denotation, connotation, and myth. The method used is descriptive qualitative by examining relevant scenes and dialogues in the series. The results show that myths construct Minangkabau culture as a value system that remains relevant in modern life, especially in regulating family economic responsibilities, the division of roles between men and women, and conflict resolution through deliberation. The series represents Minangkabau customs as a guide to life that adapts to the social and economic dynamics of contemporary society.